Synergistic effect of solute and strain on the electrochemical degradation in representative Zn-based and Mg-based alloys. (1st August 2021) - Wei, B.; Legut, D.; Sun, S.; Wang, H.T.; Shi, Z.Z.; Zhang, H.J.; Zhang, R.F.
Graphical abstract: Highlights: Li can significantly decrease the degradation rate for Mg-based and Zn-based alloys. Both tensile and compressive strain would promote the anode dissolution rate of both Mg-based and Zn-based alloys. Tensile and compressive strain can increase the strain energy and decrease the energy barrier of reaction. Electron polarization between solute atoms and solvent atoms are the main causes of the change of surface properties. Abstract: Using density functional theory and an improved Butler-Volmer model, we comparatively investigate the underlining mechanisms of solute alloying and mechanical straining on the electrochemical polarization and degradation behaviors of both Mg-based and Zn-based alloys. Our results suggest that some elements such as Li can potentially decrease the degradation rates for both alloys, while others like Fe, Ni, Cu, and Al, will play an opposite effect. By introducing the scaled strain energy to study the strain effect on the degradation kinetics of both alloys, we further reveal that both tensile and compressive strain would promote the degradation rate by decreasing the activation energy barrier.